2017
DOI: 10.1016/j.jash.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Race and sex differences in ambulatory blood pressure measures among HIV+ adults

Abstract: Ambulatory blood pressure monitoring (ABPM) can identify phenotypes that cannot be measured in the clinic. Determining race and sex disparities in ABPM measures among HIV+ individuals may improve strategies to diagnose and treat hypertension in this high risk population. We compared ABPM measures between 24 African American and 25 white HIV+ adults (36 men and 13 women). Awake systolic BP (SBP) and diastolic BP (DBP) were similar in African Americans and whites. After multivariable adjustment, sleep SBP and DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…on ABPM profiles in HIV. [ 19 ] Thus, HIV infection itself or other non- traditional potential risk factors for non-dipping BP such as: mood disorders, psychosocial stress and poor sleep quality need to be considered. Health care providers should consequently be attentive towards diagnosing psychosocial stressors and mood disorders, depression in particular, which are the most frequent psychiatric complication associated with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on ABPM profiles in HIV. [ 19 ] Thus, HIV infection itself or other non- traditional potential risk factors for non-dipping BP such as: mood disorders, psychosocial stress and poor sleep quality need to be considered. Health care providers should consequently be attentive towards diagnosing psychosocial stressors and mood disorders, depression in particular, which are the most frequent psychiatric complication associated with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies suggest a greater prevalence of nocturnal non-dipping BP in HIV-uninfected African Americans compared to their white counterparts. [ 18 , 19 ] However, ABPM patterns have been scarcely described in HIV-infected or uninfected black African populations. A South African study, comparing ABPM in black and Indian-ancestry medical students, revealed less nocturnal dipping and a higher left ventricular mass in the black students.…”
Section: Introductionmentioning
confidence: 99%
“…This neuro-endocrine hyperactivity may be partially explained by psychosocial influences that have been shown to a play a role in hypertension, with investigators implicating stressors such as HIV-related stigma and mood disorders in autonomic dysfunction and disturbances of circadian rhythm. 8890 The influence of circadian rhythm derangement is further supported by the observation that, even among HIV-infected individuals who did not meet diagnostic criteria for hypertension, there was a greater likelihood of elevated nocturnal pressures and a lesser incidence of dipping systolic blood pressure, both of which may be harbingers of impending hypertension. 88,91,92…”
Section: Mechanismsmentioning
confidence: 97%
“…Some studies with HIV-infected patients conducted in South Africa also found a high proportion of MH, and other study conducted in United States shows a prevalence higher among African Americans than among whites. 39 - 41 Furthermore, high prevalence of MH had already been described in African Americans in large cohorts of non-HIV-infected population. 42 Additionally, the ICH proportion in patients previously diagnosed with hypertension is similar to that of our cohort, according to other authors.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of patients with MH were diagnosed because they had nocturnal hypertension, which is exclusively diagnosed by ABPM. Nocturnal hypertension has been previously described in HIV-infected patients, especially among African Americans, 41 and it is considered that it has similar causal mechanisms with nondipper pattern. Nondipper pattern was found more frequently in HIV-infected than in non-HIV patients in previous case-control studies.…”
Section: Discussionmentioning
confidence: 99%